Making silicone rubber highly resistant to bacterial attachment using thiol-ene grafting - Magennis, Eugene Peter; Hook, Andrew L.; Williams, Paul; Alexander, Morgan R. (American Chemical Society, 2016)
Biomedical devices are indispensable in modern medicine yet offer surfaces that promote bacterial attachment and biofilm formation, resulting in acute and chronic healthcare-associated infections. We have developed a simple method to graft acrylates to silicone rubber, polydimethylsiloxane (PDMS), a commonly used device material that is often colonized by bacteria. We demonstrate a novel method whereby nontoxic bacteria attachment-resistant polymers can be readily grafted from and grafted to the surface using thiol-ene chemistry, substantially reducing bacterial colonization. With use of this approach, bacterial biofilm coverage can be reduced by 99% compared with standard PDMS in an in vitro assay. This grafting approach offers significant advantages over commonly used physisorbed coatings, especially in areas of high shear or mechanical stress. Furthermore, the approach is versatile such that the grafted material properties can be tailored for the desired final application.